English Language Teacher Candidates’ Pedagogical Beliefs During Covid19 Pandemic - Çetin Köroğlu, Zeynep (LPPM Universitas Advent Indonesia, 2023)
The pandemic has been affecting every side of our lives in a negative way unfortunately. Teacher training has also been affected from the pandemic and student teachers have been taken their courses through digital environments. Unlike traditional courses they have to study the entire courses online. As it is known that teachers’ beliefs have a profound impact on their classroom practices, decisions on their teaching strategies, their styles and even how they implement curriculum. For this reason, the current study aims to investigate whether Covid19 pandemic has an effect on student teachers’ beliefs positively or negatively. The research was carried out in 2020 spring term of academic year when the pandemic first started. The research was designed as a qualitative study and to collect data a case and an interview administered to participants. Totally, 74 student teachers participated in the study that participants were third and fourth graders of ELT department at a state university, Turkey. The results indicate that participants have negative perspectives towards taking all courses through digital environments and tools. However, their beliefs have not been affected negatively from Covid19 pandemic.